Thyroid Cancer : an Overview of Epidemiology, Risk Factor, and Treatment - Arista, Rida Dwi; Khaula Karima; M. Fardi Anugrah; Puji Widyastuti; Eva Triani (Faculty of Medicine, Universitas Mataram, 2023)
Thyroid cancer is the most common cancer of the endocrine glands with a prevalence of approximately 95% of all malignancies. Its incidence has increased more rapidly since the 1990s than any other cancer. Thyroid cancer is divided into 4 types based on its histopathology. The nature of this cancer varies, ranging from slow progressive to aggressive. Like other cancers, thyroid cancer if left untreated will invade other organs of thebody. We collect several reading journals that discuss epidemiology, risk factors, management for thyroid gland cancer and present them descriptively. The purpose of writing this article is to discuss the latest epidemiology and risk factors that influence the incidence of thyroid cancer as well as the old and newest treatments in treating thyroid cancer. The results of this article found several risk factors thought to influence prevalence, namely radiation exposure, genetic mutation, heredity, iodine deficiency, increased TSH, autoimmune, thyroid nodules, environment, lifestyle, and estrogen. Treatments that need to be carried out are surgery, RAI therapy, thyroid hormone therapy, external radiation, systemic chemotherapy, and combination therapy. Through this discussion, it is hoped that it can become material for analysis and reference in the treatment of thyroid gland cancer. Keyword : Thyroid cancer, epidemiology, risk factor, and treatment